Consumer Acceptance Test of Purple Uwi (Dioscorea Alata L) Mousse Tape - Triastuti, U. Yuyun (Jurnal Indonesia Sosial Sains, 2024)
Purple uwi tape mousse is a frozen dessert type of soft pudding made from the main ingredients of purple uwi tape and cream. The use of purple uwi tape, besides providing color and taste, also extends the life of the purple yam tape and adds nutritional content to the mousse. The objectives of this research are to determine the characteristics of purple uwi tape mousse, to determine consumer acceptance of purple uwi tape mousse, and to know the nutritional content of purple uwi tape mousse. The panellists' acceptance of the purple uwi tape mousse through the results of the hedonic test showed that what the panellists liked most was the mousse with the addition of 100% purple uwi tape in the M3 code. The characteristics resulting from mousse with this recipe formula are that it has a sweet, savoury, slightly salty taste, a distinctive aroma of tape and milk, a soft texture, and a bright pink color so that it attracts consumer interest. Purple uwi tape mousse nutrition per cup measuring 8 oz/ounce, or 117 g, contains 0.572 g fibre, 5.44 g protein, 0.242 g flavonoids, 41.9 g carbohydrates, and 28.1 g fat.